A revision of the endemic South African long-jawed ground spider genus Drassodella Hewitt, 1916 (Araneae: Gallieniellidae) - Mbo, Zingisile; Haddad, Charles R. (Zootaxa, 2019)
The genus Drassodella Hewitt, 1916 is one of four Afrotropical genera of Gallieniellidae, and is presently represented by seven species, all endemic to South Africa. The type material of six of the described species was studied and they are redescribed from both sexes: D. melana Tucker, 1923, D. quinquelabecula Tucker, 1923, D. salisburyi Hewitt, 1916, D. septemmaculata (Strand, 1909), D. tenebrosa Lawrence, 1938 and D. vasivulva Tucker, 1923. Of these, the males of D. melana, D. tenebrosa and D. vasivulva are described for the first time. Recent field work yielded additional females of D. purcelli Tucker, 1923 from the vicinity of the type locality, and this sex is redescribed; the male remains unknown. A further 12 new species are recognized: D. amatola sp. nov. (♀ ♂), D. aurostriata sp. nov. (♀ ♂), D. baviaans sp. nov. (♂), D. flava sp. nov. (♀ ♂), D. guttata sp. nov. (♀ ♂), D. lotzi sp. nov. (♀), D. maculata sp. nov. (♀), D. montana sp. nov. (♀ ♂), D. tolkieni sp. nov. (♀ ♂), D. trilineata sp. nov. (♀), D. transversa sp. nov. (♀ ♂) and D. venda sp. nov. (♀ ♂). Based on the genitalic structures, there appear to be two distinct species groups. The D. melana species group, which includes D. melana, D. tenebrosa and eight new species mainly distributed in eastern and northern South Africa, is characterised by very conservative genitalic morphology in both sexes. The D. salisburyi species group, with considerable variation in the structure of the copulatory organs and distributed in the southern half of South Africa, includes the remaining nine species, of which four are new. Although D. tenebrosa represents an intermediate between the two groups, with palpal morphology more typical of the D. melana species group and epigynal morphology typical of the D. salisburyi group, it is placed in the former species group based on its distribution in eastern South Africa. The biology, habitat preferences and biogeography of Drassodella are briefly discussed.